Propolis and essential oils additives in the diets improved animal performance and feed efficiency of bulls finished in feedlot - Maribel Velandia Valero; Rodolpho Martin do Prado; Fernando Zawadzki; Carlos Emanuel Eiras; Grasiele Scaramal Madrona; Ivanor Nunes do Prado (Acta Scientiarum. Animal Sciences, 2014)
This work was realized to evaluate the effect of natural additives as propolis or essential oils addition on animal performance, feed intake, apparent digestibility and carcass characteristics of bulls finished in feedlot. Thirty bulls (½ Aberdeen Angus vs. ½ Nellore) were randomly assigned in one of three diets (control – CON, propolis – PRO and essential oils – OIL) and kept in feedlot (individual pen) during 55 days. CON diet consists of 45% corn silage, 40% concentrate (cracked corn, soybean meal, limestone and mineral salt) and 15% glycerine. The PRO group received same diet that control plus 3 grams to animal day-1 of propolis dry added to the concentrate. The OIL oils group received same diet that control and 3 grams to animal day-1 of essential oils (cashew and castor oils) added to the concentrate. Final weight, average daily gain, feed efficiency and hot carcass weightwere better for bulls supplemented with essential oils and propolis than for bulls fed control diet. The feed intake, apparent digestibility, carcass conformation and tissue composition were unaffected by the additives addition. The addition of propolis and essential oils in the diets of bulls finished in feedlot improve animal performance and carcass weight.